PERMAINAN ULAR TANGGA MENINGKATKAN PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR DALAM PENCEGAHAN IMPAKSI SERUMEN DI SDN TAMBAKSARI III SURABAYA - Norma Astrianingsih; Kristiawati Kristiawati; Ilya Krisnana (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Cerumen impaction is syndrome of hearing due to the build up of ear wax in the ear canal and cause pressure that impair. It is found in elementary school children. Cleanliness of child's ears cannot clean because the children afraid if other objects put in their ears and children’s has less knowledge and attitude about the impact of dirty ears. Health education using the snake ladders game can be applied as a solution to this problem. The purpose of this research is explain effect of snake ladders game towards elementary school children’s knowledge and attitude in the prevention of cerumen impaction at SDN Tambaksari III Surabaya.Methods: This research used quasy experimental design and object of this research is the childrens in third grade at SDN Tambaksari III Surabaya. The sampling used total sampling technique, based on the inclusion criteria, used 32 respondents consist of 16 people as experiment group and 16 people as control group. Data collected by quesioner and analyzed by wilcoxon signed rank test and mann whitney test with significant value p≤0,05.Result: The results showed that there were enhancement for knowledge (p=0.001), and attitude (p=0.001) for post intervention toward the experimental group. These data were strenghted by the result of Mann Whitney U Test statistical analysis that showed the significant differences for knowledge (p=0.000), and attitude (p=0.004).Discussion: It can be concluded that snake ladders game effective to enhance the children’s knowledge and attitude in the prevention of cerumen impaction. The suggestion for next researcher is to give health education using snake ladders for behavior of cerumen impaction’s prevention.